Selection of Sharia Rural Financing Bank Financing During Covid-19 Pandemic - Azhar Alam; Dicky Trio Adi Saputro (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2021)
This research discusses the selection of financing submissions for BPRS Magetan customers in the covid-19 pandemic situation. This study aims to determine the criteria for obtaining financing and how BPRS Magetan policy suppresses high financing applications amid the covid-19 pandemic. This study used a descriptive qualitative method by collecting data by conducting in-depth interviews with 14 respondents from BPRS and financing customers. This study stated that BPRS Magetan added the emphasis of analysis in selecting customer members' financing with the 5C method and BI Check. BPRS emphasizes selection analysis in customer human resource, customer creativity, and customer innovation to develop its business. BPRS Magetan is expected to provide leeway by giving a more extended time and simplifying the disbursement process during the covid-19 pandemic in the form of collateral relief.